Application of fuzzy bow-tie risk analysis to maritime transportation: The case of ship collision during the STS operation. (1st December 2020) - Arici, Seher Suendam; Akyuz, Emre; Arslan, Ozcan
Abstract: Risk analysis is of paramount importance in maritime transportation due to the particularly hazardous nature of the work. While the International Maritime Organization (IMO) has circulated Formal Safety Assessment (FSA) for the assessment of on-board risk, it has not introduced a specific tool for risk analysis, and a more proactive approach to the assessment of risk is consequently sought by maritime safety researchers. This paper aims to demonstrate how the fuzzy bow-tie method of analysis might be deployed to quantitatively analyse risk. Focussing on the specific context of ship to ship (STS) cargo operations enables specific insights into the method to be gained. The findings of the research can be utilised by maritime safety professionals (STS superintends, mooring masters, tanker safety inspectors, company fleet managers, and tanker shipowners) in order to mitigate potential risks and enhance marine safety during the STS operation. Highlights: "Application of fuzzy bow-tie risk analysing method to maritime transportation: The case of ship collision during STS operation.". The FTA and ETA method is integrated under fuzzy sets environment for risk analysis. A quantitative risk analysing is perform to minimize potential risk of collision during STS operation. Practical contributions for maritime safety professionals to minimize risk and enhance operational safety.